Carotid web stent for the prevention of recurrent stroke: Case report and literature review. Issue 2 (15th February 2022) - Alnajjar, Mohammed; Imam, Yahia Z.; Akhtar, Naveed; Habas, Elmukhtar; Zakaria, Ayman
Abstract: Carotid web has been identified as one of the missed causes of recurrent stroke. The diagnosis and management of such cases impose a challenge to medical practitioners. This etiology should be kept in mind, especially in case of recurrence of stroke in a similar cerebral territory. Abstract : A high index of suspicion toward unusual etiologies should be raised in cases of recurrent stroke in same cerebral territory. One of these usually missed causes is carotid web.